2016
DOI: 10.1007/s11665-016-2225-y
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Modeling of Al-Al and Al-Steel Friction Stir Spot Welding

Abstract: This paper presents a finite element thermal model for similar and dissimilar alloy friction stir spot welding (FSSW). The model is calibrated and validated using instrumented lap joints in Al-Al and Al-Fe automotive sheet alloys. The model successfully predicts the thermal histories for a range of process conditions. The resulting temperature histories are used to predict the growth of intermetallic phases at the interface in Al-Fe welds. Temperature predictions were used to study the evolution of hardness of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…Nonetheless it is apparent that there will be a (modest) additional contribution to plastic deformation in the swirl region, at a radius around 0.4-0.7 of the tool radius. Jedrasiak et al (2013) have used this observation to guide the calibration of the radial distributions of heat input in a thermal model developed for FSSW. This thermal model has shown that the differences in thermocouple data for welds with flat and fluted tools could be predicted successfully by using a different radial heat input distribution for each tool type.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless it is apparent that there will be a (modest) additional contribution to plastic deformation in the swirl region, at a radius around 0.4-0.7 of the tool radius. Jedrasiak et al (2013) have used this observation to guide the calibration of the radial distributions of heat input in a thermal model developed for FSSW. This thermal model has shown that the differences in thermocouple data for welds with flat and fluted tools could be predicted successfully by using a different radial heat input distribution for each tool type.…”
Section: Discussionmentioning
confidence: 99%
“…Modelling efforts such as those by Jedrasiak et al (2013) aim to predict the temperature distribution in the heat-affected zone, and at the weld interface, to interpret and model these microstructural changes. These thermal models use surface heating distributions guided by the kinematic interpretation of contact conditions provided in this paper.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not surprising, as in the Refill FSW process the highest weld temperatures are known to be reached under the sleeve where there is the greatest relative tool surface velocity. [24,44,45,48] However, when compared to the baseline sample, prepared under identical conditions, the Al(Si)-Mg joint exhibited an overall reduction of about 30 pct in the thickness of the reaction layer, despite not forming a significant quantity of Mg 2 Si. As discussed above, this improvement may be partly related to more mixing occurring with the softer cladding layer, which would be expected lead to greater dispersal of the reaction products, but another important factor to consider is if the same interface temperature was reached for each set of welds.…”
Section: E Fssw Experimentsmentioning
confidence: 97%
“…However, some local melting was observed at the extreme edge of the weld nugget (such as at site E and D in Figure 6) where the highest temperature rise is expected. [7,24,43,48] The temperature for the eutectic reaction (Mg) + c fi L occurs at approximately 709 K (436°C) by thermodynamic calculation (Figure 1(b)). This is just above the peak temperature measured in the clad Al(Si)-Mg sample [698 K (425°C) Figure 10], but must have been exceeded locally as small solidified areas containing a eutectic mixture of Al 12 Mg 17 and Mg can be observed on the Mg side of the joint (Figures 11(c) and (d)…”
Section: Weld Interface Temperaturesmentioning
confidence: 99%